Facebook Messenger: As Means of Communication for Academic Inquiries - John Erwin Pedroso; Laura Fe A. Tubola; Earl Jhon Aquidado (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
Most of social media users use Facebook Messenger as a messaging platform because of its free messaging and video chatting service. Thus, it is not a surprise that Facebook Messenger is utilized as a communication tool for academic purposes. This descriptive qualitative research anchored on the epistemology constructionism, methodology and naturalistic inquiry aimed to determine how do students use Facebook-Messenger as means of communication for academic inquiries. The aforesaid study was conducted among the twelve (12) BSED Social Studies learners who were identified through purposeful sampling. The researchers utilized a semi-structured written interview which contains one question anchored in the Task-Technology Fit (TTF) Theory. On the other hand, the data and information were collected through essay form and analyzed through Conventional Qualitative Content Analysis. In using Facebook Messenger as a means of communication for academic inquiries, the informants from BSED Social Studies expressed that the platform is avenue for academic skills, task-needs, and their preferred technology. First, informants expressed that Facebook Messenger is an avenue for academic skills because it (1) facilitates collaboration, its (2) easy navigation of features, and (3) fosters teacher-learner communication. Also, Facebook Messenger fills for their task-need as it helps them conduct (1) group discussion, (2) convenient submission, have (3) clear instruction, and (4) task clarity. Lastly, informants show evidence that the platform is their preferred technology because it is an (1) alternative platform, (2) file-sharing platform, (3) provide storage for preference, (4) up-to-date reminder, and a (5) convenient tool for communication. This study reveals that Facebook Messenger is used as a tool to open an avenue for academic skills, is an essential platform for delivering task needs, and was a preferred technology as a means of communication for academic inquiries.